Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan (Studi Pada PT. Bank Rakyat Indonesia.Tbk Tahun 2011-2013) - Widodo, Aris; , Drs. Ma'ruf, M.M (2015)
The purpose of this study was to determine the condition of the financial ratios. Bank Rakyat Indonesia Tbk 2011-2013. Samples are financial statements at PT. The People's Bank Indonesia.Tbk the form of balance sheet and income statement 2011-2013. Data analysis results can be obtained as follows: 1) The ratio of liquidity in an illiquid proven Current Ratio and Cash ratio shows that the ability of PT. Bank Rakyat Indonesia Tbk, which is on the JSE in meeting short-term obligations in the state has not been able to because of current assets are not sufficient to cover the current liabilities. Solvency ratio in 2011 in a state insolvabel shows that if the company is liquidated, the company was unable to repay all its debts both short- and long-term use of all the assets owned by the company. The solvency ratio in the years 2012-2013 solvable condition indicates that if the company is liquidated, the company is able to restore all its debts both short- and long-term use of all of the company's own capital. Profitability ratios in a state rendabel evidenced by ROA and ROE From the overall results of the analysis of the ratio of 2011 to 2013 showed a trend for profitability despite volatile or up and down. Keywords: Liquidity Ratio, Solvency and Profitability